ANALISIS UNSUR INTRINSIK PADA CERPEN “PENULIS TUA” KARYA HARYO PAMUNGKAS - nenti nurhayati (IKIP Siliwangi, 2020)
Short story is one type of literary work in the form of prose with a short story, but in the story there is a series of stories that cover the problem and its solution. Short stories are built with two elements, namely intrinsic elements and extrinsic elements. The intrinsic elements of the short story include the theme, setting, character / characterization, plot, point of view, language style and message. Extrinsic elements include community background, author background and the values contained in the short story. This research is motivated to appreciate short stories as one of the literary works, this research uses descriptive qualitative research method, the purpose of this study is to analyze and describe the intrinsic elements contained in the short stories “old writer” by Haryo Pamungkas. Data analysis was carried out in several stages, namely by reading, analyzing, taking notes and identifying the contents of the short story. After the data were analyzed, the researcher found that the short story “old writer” by Haryo Pamungkas contained intrinsic elements,namely theme, setting, plot, character / characterization, point of view, language style and mandate. The short story also has a message to convey to readers who always rely on the their devices that if life is only spent in front of a square screen that can contain everything without us knowing the outside world we will never know how beautiful it is to remember the past that was so pleasant in old age.